PENDEKATAN TEORI TECHNOLOGY ACCEPTANCE MODEL (TAM) TERHADAP PENERIMAAN SISTEM INFORMASI MANAJEMEN PADA PT. WUTAMA TRI MAKMUR - Monika Puji Lestari; Dian Parawansa; Andi Nur Bau Massepe (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study aims to determine and analyze the influence of perceived of usefulness, perceived ease of use, and attitude towards using to the acceptance of management information with Technology Acceptance Model (TAM) approach. To achieve these objectives then used data collection techniques through the distribution of questionnaires and documentation. While the data analysis techniques used are validity test, reliability test and hypothesis testing techniques, through SmartPLS 2.0 M3 application. The result of this research shows that the perceived usefulness gave negative affect to attitude toward using, perceived ease of use have a positive effect to the attitude toward using, the perceive usefulness does not give any influence to the acceptance of the management information system, the perceived ease of use and attitude toward using has a positive effect on the acceptance of management information system, PT. Wutama Tri Makmur